High ankle sprains - Minimizing the frustration of a prolonged recovery - Smith, A. H.; Bach, B. R. (The Physician and Sportsmedicine, 2004)
High ankle sprains, or syndesmotic injuries, are a distinct entity from the more common inversion ankle sprain. Dorsiflexion of the ankle, external rotation of the leg, or a combination of both can disrupt the syndesmotic ligament complex, including the anterior and posterior tibiofibular ligaments. Diagnostic maneuvers, such as the squeeze test and the external rotation test, plus radiographic findings help make the diagnosis. Less severe sprains can be treated nonoperatively with protected weight bearing, but grade 3 sprains require surgical anatomic reduction of the syndesmotic joint. If misdiagnosed or managed incorrectly, syndesmotic injuries can lead to unfavorable late sequelae. Clinicians should set realistic expectations for a long recovery period and slow return to sports.